Vulneración del principio de seguridad jurídica en funcionarios públicos médicos del seguro campesino de Loja ante la ausencia de reglamento de escalafón salarial institucional - Tapia Ramírez, Deicy del Rocío (2024)
The purpose of this work was to determine whether there is a violation of the right to equality before the law, with respect to the feeder? Focusing on the analysis of the implications of the absence of a salary scale in relation to the violation of the principle of legal certainty, which was carried out through an exhaustive study of the legal regulations in force and the applicable jurisprudence, with the purpose of demonstrating whether the lack of a regulation as a rule governing the salary structure ends up generating uncertainty, lack of predictability and demotivation in medical public servants, as well as whether the absence of a regulation undermines their rights and prevents them from being recognized on the basis of merit, training, experience and seniority. In order to achieve the stated objectives, the methodology was based on the inductive, descriptive, analytical and exegetical method, and the application of the qualitative .Likewise, techniques of documentary theoretical collection were introduced, concomitantly, surveys were conducted to legal professionals, whose questions were outlined with topics of legal security, effects, importance of the regulations, among other topics that were of benefit in the present study in order to verify the diverse criteria of the actors and to obtain viable information in the development of the problem.Relevant information was obtained on the research topic, evidencing that there really exists a violation within the principle of legal security, reaching the conclusion that it is necessary as legal professionals to contribute with our knowledge as recommendations focused on the implementation of a regulation of the career ladder in the medical public servants of the Peasant Social Security, achieving with this favors the stability and predictability of the rules in the Ecuadorian State, to thereby reaffirm the enjoyment of the fundamental rights of people, and also ensures that people can be aware of the legal consequences that may occur when there is omission or violation by any administrative act that seeks to nullify or impair the rights of public servants.